Implementasi Protokol Neighbor Discovery Pada Pembentukan Komunikasi Antara Node Sensor dan IoT Middleware Berbasis Jaringan 6LoWPAN - Heru Dias Pambudhi; Eko Sakti Pramukantoro; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
6LoWPAN is a network technology that is proven for IoT environment to facilitate the transmission of data from sensor node to IoT middleware. The advantages of 6LoWPAN are it is suitable for low-power device and has high scalability because it is based on IPv6. But, there is a challenge in forming communication between node sensor and the IoT middleware in 6LoWPAN, i.e. node sensor can't find out the existence and the middleware address. Beside that, node sensor also can't self-configured it's IP address using the prefix that is provided by the middleware. These problems can be resolved with Neighbor Discovery Protocol (NDP), which can give node sensor the ability to automatically find out the middleware existence and address also can self-configured it's IP address. NDP can be applied with radvd program on the middleware side and ndisc6 program on the node sensor side. The result of this research are node sensor can find out the existence and the middleware address, automatic IP addressing in node sensor, discovery delay around 1ms , the number of exchanged NDP control message of each node is six, packet delivery ratio of CoAP and MQTT are 93% and 100%, and the maximum reachability range is 105m.